2020
DOI: 10.1016/j.cub.2020.01.050
|View full text |Cite
|
Sign up to set email alerts
|

Specific Eco-evolutionary Contexts in the Mouse Gut Reveal Escherichia coli Metabolic Versatility

Abstract: Members of the gut microbiota are thought to experience strong competition for nutrients. However, how such competition shapes their evolutionary dynamics and depends on intraand interspecies interactions is poorly known. Here we tested the hypothesis that Escherichia coli evolution in the mouse gut is more predictable across hosts in absence of interspecies competition than in the presence of other microbial species. Supporting this hypothesis, we observed a specific genetic adaptation in lrp, a gene encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 105 publications
(132 reference statements)
8
69
0
Order By: Relevance
“…These markers allow rapid detection of evolutionary adaptation to the gut through the emergence and spread of new mutations within the focal newly colonizing strains. The short treatment with streptomycin is able to break colonization resistance, allowing the invader E. coli to colonize the mouse gut under a complex gut microbiota, which may harbor a resident E. coli strain [6] and can affect its evolutionary trajectories [7].…”
Section: Resultsmentioning
confidence: 99%
“…These markers allow rapid detection of evolutionary adaptation to the gut through the emergence and spread of new mutations within the focal newly colonizing strains. The short treatment with streptomycin is able to break colonization resistance, allowing the invader E. coli to colonize the mouse gut under a complex gut microbiota, which may harbor a resident E. coli strain [6] and can affect its evolutionary trajectories [7].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, bacteria are forced to interact with other microbes upon colonization or infection of the host. In the process, commensal microbes impact the eco-evolutionary dynamics by affecting traits under selection (61). For example, monocolonization of the mouse gut by E. coli can lead to predictable bacterial metabolic adaptations through the selection of mutations in genes related to amino acid metabolism, a process that is, however, altered by co-colonization with other microbes (61).…”
Section: Host-microbiome-pathogen Interactionmentioning
confidence: 99%
“…In the process, commensal microbes impact the eco-evolutionary dynamics by affecting traits under selection (61). For example, monocolonization of the mouse gut by E. coli can lead to predictable bacterial metabolic adaptations through the selection of mutations in genes related to amino acid metabolism, a process that is, however, altered by co-colonization with other microbes (61). Another example is colonization resistance, where presence of a complex residing microbial community can protect against pathogen infections (62).…”
Section: Host-microbiome-pathogen Interactionmentioning
confidence: 99%
“…Historically the model systems available to study intestinal epithelial-microbe interactions consisted primarily of immortalized cell lines and animal models. For instance, germ-free mice have become the gold-standard for investigating host and microbial responses during the establishment of defined bacterial populations within the microbe-naïve gut (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, while a number of factors contribute to bacterial intestinal colonization, the ability to compete for a limited number of nutritional niches is paramount for successful colonization of the gut(35,36). In addition, several studies have demonstrated that nutrient availability is the primary driver of E. coli colonization and adaptation within the murine gut(9,35,37). Thus, competition may increase the nutritional stress within the germ-free mouse intestine, though perhaps not to the same degree as that inherent to the HIO lumen.…”
mentioning
confidence: 99%